Biodiesel from microalgae lipids: from inorganic carbon to energy production. Issue 2 (4th March 2018) - Veillette, Marc; Giroir-Fendler, Anne; Faucheux, Nathalie; Heitz, Michèle
ABSTRACT: Following the United Nations Conference on Climate Change, COP21 (Paris, France), several countries have attempted to reduce their greenhouse gas emissions. In order to reach this objective, microalgae could be used to capture carbon dioxide and transform it into a biomass composed essentially of lipids, carbohydrates and proteins. Moreover, cultivating microalgae does not require arable land, in opposition to several oleaginous plants used to produce biofuels. Despite the fact that microalgae could be transformed into several biofuels such as bioethanol (by fermentation of hydrocarbons) and biomethane (by anaerobic digestion), transforming lipids into biodiesel could allow the reduction of oil-based diesel consumption. However, microalgae biodiesel production costs remain high for a short-term commercialization. The microalgae lipids can be transesterified into biodiesel in the presence of catalysts (homogeneous or heterogeneous). In order to commercialize biodiesel from microalgae, biodiesel physicochemical properties must respect the American Society for Testing and Materials (ASTM) standards. The aim of the study was to describe the current technologies available to produce biodiesel from microalgae.